The influence of new severe plastic deformation on microstructure, mechanical, and corrosion properties of Mg-0.8Mn-0.5Ca alloy (Journal of Mining and Metallurgy, Section B: Metallurgy, 2023)
In this research, the effect of accumulative extrusion bonding (AEB) on the microstructure and mechanical properties of Mg-0.8Mn-0.5Ca biocompatible alloy was investigated. The goal of this research was to develop the mechanical and corrosion properties of Mg-0.8Mn-0.5Ca alloy after ABE process as a novel severe plastic deformation process. The simulation of AEB process showed that the average effective strain per pass for channels with the internal angle of 120 was about 1.93. The average grain size was dramatically decreased from about 448.3 µm for the homogenized alloy to 1.55 µm for the 3-pass processed sample. Microstructural observations suggested a combination of continuous, discontinuous, and twinning-induced dynamic recrystallization as the major mechanisms of grain refinement. Tensile and compressive strengths were improved from 150 and 205 MPa to 330 and 301 MPa after three passes of AEB, indicating 2 and 1.5 times improvements, respectively. Tensile elongation decreased from 26% for the homogenized sample to 7.5% for the 3-pass processed sample due to the severe work-hardening, non-uniform strains, and inhomogeneous microstructure produced by the ABE process. Corrosion resistance in SBF solution was improved from 1.1 to 14.159 〖KΩ Cm〗^2 after three passes of ABE due to the presence of hydroxyapatite formed on the surface of the AEBed samples.
Keywords: Severe plastic deformation; Dynamic recrystallization; Hydroxyapatite; Hydrogen evolution; EIS test; Biocompatible